Overlooked organic vapor emissions from thawing Arctic permafrost - Haiyan Li; Minna Väliranta; Mari Mäki; Lukas Kohl; A Britta K Sannel; Jukka Pumpanen; Markku Koskinen; Jaana Bäck; Federico Bianchi (Environmental Research Letters, 2020)
Volatile organic compounds (VOCs) play an essential role in climate change and air pollution by modulating tropospheric oxidation capacity and providing precursors for ozone and aerosol formation. Arctic permafrost buries large quantities of frozen soil carbon, which could be released as VOCs with permafrost thawing or collapsing as a consequence of global warming. However, due to the lack of reported studies in this field and the limited capability of the conventional measurement techniques, it is poorly understood how much VOCs could be emitted from thawing permafrost and the chemical speciation of the released VOCs. Here we apply a Vocus proton-transfer-reaction time-of-flight mass spectrometer (PTR-TOF) in laboratory incubations for the first time to examine the release of VOCs from thawing permafrost peatland soils sampled from Finnish Lapland. The warming-induced rapid VOC emissions from the thawing soils were mainly attributed to the direct release of old, trapped gases from the permafrost. The average VOC fluxes from thawing permafrost were four times as high as those from the active layer (the top layer of soil in permafrost terrain). The emissions of less volatile compounds, i.e. sesquiterpenes and diterpenes, increased substantially with rising temperatures. Results in this study demonstrate the potential for substantive VOC releases from thawing permafrost. We anticipate that future global warming could stimulate VOC emissions from the Arctic permafrost, which may significantly influence the Arctic atmospheric chemistry and climate change.